The Relationship between Fluid Flow, Structures, and Depositional Architecture in Sedimentary Rocks: An Example-Based Overview - Vilde Dimmen; Atle Rotevatn; Casey W. Nixon (Geofluids)
Fluid flow in the subsurface is fundamental in a variety of geological processes including volcanism, metamorphism, and mineral dissolution and precipitation. It is also of economic and societal significance given its relevance, for example, within groundwater and contaminant transport, hydrocarbon migration, and precipitation of ore-forming minerals. In this example-based overview, we use the distribution of iron oxide precipitates as a proxy for palaeofluid flow to investigate the relationship between fluid flow, geological structures, and depositional architecture in sedimentary rocks. We analyse and discuss a number of outcrop examples from sandstones and carbonate rocks in New Zealand, Malta, and Utah (USA), showing controls on fluid flow ranging from simple geological heterogeneities to more complex networks of structures. Based on our observations and review of a wide range of the published literature, we conclude that flow within structures and networks is primarily controlled by structure type (e.g., joint and deformation band), geometry (e.g., length and orientation), connectivity (i.e., number of connections in a network), kinematics (e.g., dilation and compaction), and interactions (e.g., relays and intersections) within the network. Additionally, host rock properties and depositional architecture represent important controls on flow and may interfere to create hybrid networks, which are networks of combined structural and stratal conduits for flow.